Dense Ti3AlC2 based materials obtained by SHS-extrusion and compression methods. Issue 2 (1st February 2019) - Pazniak, A.; Bazhin, P.; Shchetinin, I.; Kolesnikov, E.; Prokopets, A.; Shplis, N.; Stolin, A.; Kuznetsov, D.
Abstract: MAX phases (M: early transitionA:13 and 14 group A-element; X:C and/or N) are ternary carbides/nitrides with a unique combination of metallic and ceramic properties. Bulk MAX phases can be prepared from different starting materials and pre-synthesized powders mostly at high temperature and long sintering time. Here, we prove an efficient one-step technological method to produce bulk MAX phase based materials using self-propagation high-temperature synthesis. We show that bulk materials (relative density of 95.5% and 97.2%) can be produced in the form of plates and rods with 67.5% wt. and 81.9% wt. of MAX phases. The compressive strength of 720 ± 2 and 641.5 ± 2 MPa Young's modulus of 221.5 ± 4 and 198.3 ± 2.8 GPa, and thermal conductivity of 22.9 and 22.3 W m −1 K −1 are achieved as a result of extrusion and compression self-propagation high-temperature synthesis. The sintered materials are good thermal conductors with high mechanical characteristics that can be used as promising materials for high-temperature application.